Understanding the Mechanisms of Recovery and/or Compensation following Injury - Michael J. Hylin; Abigail L. Kerr; Ryan Holden (Neural Plasticity)
Injury due to stroke and traumatic brain injury result in significant long-term effects upon behavioral functioning. One central question to rehabilitation research is whether the nature of behavioral improvement observed is due to recovery or the development of compensatory mechanisms. The nature of functional improvement can be viewed from the perspective of behavioral changes or changes in neuroanatomical plasticity that follows. Research suggests that these changes correspond to each other in a bidirectional manner. Mechanisms surrounding phenomena like neural plasticity may offer an opportunity to explain how variables such as experience can impact improvement and influence the definition of recovery. What is more, the intensity of the rehabilitative experiences may influence the ability to recover function and support functional improvement of behavior. All of this impacts how researchers, clinicians, and medical professionals utilize rehabilitation.